2021
DOI: 10.1038/s41598-020-80507-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of subnetworks mediated by $$\hbox {TNF}\alpha$$, IL-23/IL-17 and IL-15 in a network involved in the pathogenesis of psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease clinically characterized by the appearance of red colored, well-demarcated plaques with thickened skin and with silvery scales. Recent studies have established the involvement of a complex signalling network of interactions between cytokines, immune cells and skin cells called keratinocytes. Keratinocytes form the cells of the outermost layer of the skin (epidermis). Visible plaques in psoriasis are developed due to the fast proliferation and unusual differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We also observed that the route of the plaque formation and or progression of psoriasis could be via a gradual or switch-like increase in the population of keratinocytes. This switch-like behavior could be used as a new treatment strategy, as argued in a few recent studies (Pandey et al, 2021;Pandey et al, 2023). TABLE 1 IL-36 cytokines with their source and effect on different cell types.…”
Section: Introductionmentioning
confidence: 90%
“…We also observed that the route of the plaque formation and or progression of psoriasis could be via a gradual or switch-like increase in the population of keratinocytes. This switch-like behavior could be used as a new treatment strategy, as argued in a few recent studies (Pandey et al, 2021;Pandey et al, 2023). TABLE 1 IL-36 cytokines with their source and effect on different cell types.…”
Section: Introductionmentioning
confidence: 90%
“…In a xenograft psoriasis mouse model, in vivo injection of anti-IL-15 monoclonal antibodies significantly reduced epidermal hyperplasia, dyskeratosis, and inflammatory cell infiltration, demonstrating these findings. 133 Pandey et al 134 demonstrated the link between IL-15 and T-cells, dendritic cells, and keratogenic through a numerical model of the network developed. Results after analyzing the dynamics of sub-networks involving IL-15 suggest that increased intracellular levels of IL-15 may lead to a substantial increase in keratogenic cell populations, thus causing psoriasis.…”
Section: Il-15 and Psoriasismentioning
confidence: 99%
“…Histopathologically, psoriasis has three principal features: abnormal keratinocyte proliferation, dilated blood vessels, and a dermal inflammatory infiltration of immune cells, including macrophages, MCs, neutrophils, and lymphocytes [ 133 ]. It is well established from research on human and mouse models that the TNF-α-IL-23-IL-17 axis plays a central role in the pathogenesis of psoriasis [ 135 , 136 ]. In accordance with this, FDA-approved biologic agents targeting this axis have shown high efficacy for psoriasis treatment [ 137 , 138 ].…”
Section: Modalities Of Mast Cell–cd8 T Cell Interactions In the Skin:...mentioning
confidence: 99%